RETAILERS' PERCEPTION OF MEDAN CITY MAIN MARKET RELOCATION - Syahfitra Muhammad; Nursamsi Nursamsi (LPPM Universitas Malikussaleh - Indonesia, 2023)
This study aims to analyze the perceptions of retailers towards the relocation of the main market in Medan City from five aspects, namely, accessibility, convenience, quality of vegetables and fruit, completeness of vegetables and fruit and price. Research method In general, retailers have good perceptions and are willing to move markets, but not all retailers have good perceptions of the five aspects. Convenience, quality of vegetables and fruit, and price received good perceptions. Meanwhile, accessibility to the market gets a negative perception from retailers. Accessibility to the relocated market is very limited. Both in terms of location far from the city center, the existence of limited public transportation, and expensive transportation costs. This is one of the reasons retailers are reluctant to be relocated and some who have been relocated choose shopping locations to other markets. Keywords: Relocated, Market, Perceptions